2008
DOI: 10.4049/jimmunol.180.2.1258
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Degradation of Myelin Basic Protein Peptides by Serum Autoantibodies: Novel Biomarker for Multiple Sclerosis

Abstract: The pathologic role of autoantibodies in autoimmune disease is widely accepted. Recently, we reported that anti-myelin basic protein (MBP) serum Abs from multiple sclerosis (MS) patients exhibit proteolytic activity toward the autoantigen. The aim of this study is to determine MBP epitopes specific for the autoantibodies in MS and compare these data with those from other neuronal disorders (OND), leading to the generation of new diagnostic and prognostic criteria. We constructed a MBP-derived recombinant “epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 51 publications
(43 reference statements)
6
101
1
Order By: Relevance
“…In their study, all three peptides showed significantly higher antibody levels in the PPMS/SPMS group compared with the healthy group. Moreover, we filtered "DTGILDSIG-RFFGGD" (MBP 168 -182) as frequently bound by sera of PPMS patients (supplemental File S6), which is also in accordance with the findings by Belogurov et al (46). The region MBP 257-276 forms a flexible loop at the protein surface (Fig.…”
Section: Figsupporting
confidence: 77%
See 1 more Smart Citation
“…In their study, all three peptides showed significantly higher antibody levels in the PPMS/SPMS group compared with the healthy group. Moreover, we filtered "DTGILDSIG-RFFGGD" (MBP 168 -182) as frequently bound by sera of PPMS patients (supplemental File S6), which is also in accordance with the findings by Belogurov et al (46). The region MBP 257-276 forms a flexible loop at the protein surface (Fig.…”
Section: Figsupporting
confidence: 77%
“…Belogurov et al tested 12 peptides covering the MBP sequence (isoform 5) for serum IgG reactivities (46). Three of their peptides overlapped with the peptide MBP 257-276 ("PGFGYGGRASDYKSAHKGFK"), which was filtered as PPMS-specific in our CSF IgG data set (Table III).…”
Section: Figmentioning
confidence: 99%
“…Surface plasmon res- onance studies confirmed that the serum antibodies from the AIDP patients did not bind MBP. Similarly, we failed to detect any catalytic activity of the antibodies against MOG and MBP (data not shown), the latter of which was previously shown to be hydrolyzed by autoantibodies in MS (52,53).…”
Section: Csf Protein Concentration Analyses-csf Protein Levelmentioning
confidence: 64%
“…Besides, antibodies to several proteins in the nodal area of the peripheral nerves -in particular, gliomedin, neurofascin, contactin (63,64), and moesin (65) -were found in the blood stream of some AIDP patients. We also tested blood samples against the CAM proteins whose fragments we observed.A slightly enhanced titer of autoantibodies was found only against NrCAM and the difference was not as evident as in other classic autoimmune diseases with their autoantigens (53,66). Thus, the degradation of the abovementioned proteins seems to have been associated with factors other than the autoreactive antibodies to those proteins.…”
Section: Discussionmentioning
confidence: 97%
“…In MS and SLE, anti-MBP abzymes with proteolytic activity can attack MBP of the myelin-proteolipid sheath of axons. The established MS drug Copaxone was shown to be a specific inhibitor of abzymes with MBP-hydrolyzing activity [128]. One cannot exclude that the same drugs can be used for the treatment of SLE and other autoimmune diseases, which characterized by high level of abzymes with nuclease and MBP-hydrolyzing activities.…”
Section: Lupusmentioning
confidence: 99%